Inulina e estreptococcus salivarius reduzem a halitose associada à saburra lingual: um ensaio clínico randonizado - Mousquer, Camila Rafaela (2016)
Halitosis associated with tongue coating results from the production of volatile sulfur compounds by bacterial action. The use of prebiotics and probiotics could be useful in treating such condition. Objective: To evaluate the effect of the combination of prebiotic inulin and probiotic Streptococcus salivarius (SS) in patients with halitosis by coating. Methods: In this double-blind, randomized trial, 45 patients (35 ± 15 years, 66% women) with hal itosis by coating were allocated to three treatment groups using gum of oral dissolution for 10 days, containing: inulin+SS, SS and plabebo. Organoleptic test, halimeter, coating index and evaluation of quality of life (OHIP-14 and WHOQOL-Bref) were performed before and after treatments. Generalized estimating equations were used to evaluate the effects. Results: Forty-four patients (97%) completed the study. Patients treated with inulin+SS showed greater reduction in halitosis measured by halimeter as compared to both SS only (before/after treatment: 180.5/99.7 ppb vs 197.1/125.1; p = 0.049) and placebo (before/after treatment: 180.5/99.7 ppb vs. 186.9/149.1; p = 0.002). Quality of life improved in both groups containing SS, but whithout superiority between them. Conclusions: In this phase IIa clinical trial the combination of inulin and Streptococcus salivarius was superior in controlling halitosis by coating as compared to Streptococcus salivarius only and placebo.